HUBUNGAN POLA ASUH ORANGTUA TERHADAP PERUBAHAN EMOSIONAL REMAJA DI SMP IT AL-KINDI PEKANBARU TAHUN 2019 - Andri Ani (Health Care Media, 2020)
Teenagers is a transitional period in the span of human life, connecting right-childhood and adulthood which includes biological, cognitive, and social emotional changes. Old people are the main role takers in taking care of their children. Parenting is a pattern of behavior that parents use to connect with children. This study aims to” Relationship Between Parenting Parents Towards The Emotional Changes Of Adolescents In Junior High School It Of Al-Kindi Pekanbaru In 2019". This research is quantitative with analytical design using cross sectional. Conducted on 12 February -13 February 2019 on the same it al-kindi pekanbaru. The total population is 87 people using total population, this research instrument uses a questionnaire, univariate data processing is presented in the form of a frequency distribution table followed by bivariate analysis using SPSS vs. 17. Software then presented descriptively and analytically through statistical tests. The results of the study revealed that the majority of parents used democratic parenting as many as 68 respondents (98.9%) had changes in teenage emotions that were masking as many as 54 adolescents (62.1%). From the results of the chi.square test, it was found that there was no significant relationship between parenting toward the emotional changes of adolescents in junior high school in 2019. Through this study parents were expected to provide better parenting so that the teenagers were more open with parents and teenagers experiencing good emotional development.